Gross Regional Domestic Product And Its Impact On Regional Tax Revenue In Buru District - Wahyuningsih, Tri (BALANCE: Economic, Business, Management and Accounting Journal, 2025)
Optimization of tax revenue is essential to achieve the ultimate goal of improving public welfare through the allocation of tax funds. Regional tax revenue in Buru Regency has not shown an increasing trend every year, and one of the factors influencing regional tax revenue is GRDP. The focus of this study is on which sector of GRDP needs more attention to increase regional tax revenue. This study aims to determine the effect of GRDP on tax revenue in Buru Regency, where GRDP is classified into primary, secondary, and tertiary sectors. This study was conducted using 10 secondary data sets from 2015 to 2024 with the help of the SPSS application. This study concludes that the primary sector GRDP, secondary sector GRDP, and tertiary sector GRDP have a significant and positive influence on regional tax revenue in Buru Regency. Simultaneously, the three independent variables have a substantial effect on regional tax revenue. The variables with the most significant impact on tax revenue, in sequence, are the secondary sector GRDP, primary sector GRDP, and tertiary sector GRDP. Thus, in an effort to increase regional tax revenue through increasing GRDP, the order of sectors that need attention/priority is secondary sector GRDP, primary sector GRDP, and finally, tertiary sector GRDP